2000
DOI: 10.1016/s0005-2736(99)00217-5
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a fusion mechanism between a fluid bactericidal liposomal formulation and bacterial cells

Abstract: It was previously demonstrated that fluid liposomal-encapsulated tobramycin, named Fluidosomes, was successful in eradicating mucoid Pseudomonas aeruginosa in an animal model of chronic pulmonary infection, whereas free antibiotic did not reduce colony-forming unit (CFU) counts (C. Beaulac et al., Antimicrob. Agents Chemother. 40 (1996) 665-669; C. Beaulac et al., J. Antimicrob. Chemother. 41 (1998) 35-41). These liposomes were also shown to be bactericidal in in vitro tests against strong resistant P. aerugin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 26 publications
1
91
0
1
Order By: Relevance
“…Beaulac and Sachetelli [28,32] demonstrated that liposomes consisting of tobramycin encapsulated in DPPC/DMPG 18:1 showed decreases in the bacterial counts in a sub-MIC concentration. In our experiments, the same formulation containing meropenem or gentamicin showed a bactericidal efficacy equal to or much lower than that of the free drug, depending on the bacterial strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beaulac and Sachetelli [28,32] demonstrated that liposomes consisting of tobramycin encapsulated in DPPC/DMPG 18:1 showed decreases in the bacterial counts in a sub-MIC concentration. In our experiments, the same formulation containing meropenem or gentamicin showed a bactericidal efficacy equal to or much lower than that of the free drug, depending on the bacterial strain.…”
Section: Discussionmentioning
confidence: 99%
“…bacterial resistance related to the permeability barrier and enzymatic hydrolysis by a fusion process between the liposomes and bacterial membranes [32]. There are many benefits to using liposomes as antibiotic carriers, and there are ongoing studies to find new liposomal forms of drugs.…”
Section: Cell Mol Biol Lett 362mentioning
confidence: 99%
“…[35] The explanation for this difference with tobramycin is likely an interaction between meropenem and the liposomal membrane that inhibits the fusion between bacteria and the liposomes. [34] Increased antimicrobial activity of amikacin, gentamicin and tobramycin containing liposomes either composed of DPPC:Chol or DSPC:Chol was observed in P. aeruginosa or Burkholderia cenocepacia biofilms respectively. Fusion of these liposomes with the bacteria was also proven by a combination of flow cytometry, lipid mixing, TEM and immunochemistry techniques as mentioned above.…”
Section: Fusogenic Liposomesmentioning
confidence: 98%
“…In addition, the electron microscopy images showed close contact between the liposomes and the outer membrane of the bacteria (Figure 2 C). [34] Surprisingly, when the Fluidosomes™ were loaded with meropenem, higher MIC values compared to the free antibiotic were obtained in P. aeruginosa biofilms. [35] The explanation for this difference with tobramycin is likely an interaction between meropenem and the liposomal membrane that inhibits the fusion between bacteria and the liposomes.…”
Section: Fusogenic Liposomesmentioning
confidence: 99%
“…They can be also utilized in dermatology as a local drug depot in combination with penetration enhancers (de Leeuw et al, 2009;Pierre & Dos Santos Miranda Costa, 2011;Puglia & Bonina, 2012;Rahimpour & Hamishehkar, 2012). Furthermore, as antimicrobial drug delivery carriers, liposomes are able to enhance antibiotic concentrations at the site of infection (passive or active targeting), increase bactericidal efficacy (via fusion with the bacterial membrane), improve drug uptake and decrease the toxicity of potentially toxic antimicrobial agent (Fresta et al, 1995;Sachetelli et al, 2000;Mugabe et al, 2006b;Halwani et al, 2008, Drulis-Kawa et al, 2009.…”
Section: The Advantages Of Liposomes As Drug Carriersmentioning
confidence: 99%